Knockout of purinergic receptor Y13 (P2Y13) results in an improved outcome of metabolic syndrome in mice. (25th November 2020) - Merz, J; Rofa, K; Karnbrock, L; Von Garlen, S; Dimanski, D; Koenig, S; Bulatova, K; Schaefer, I; Peikert, A; Albrecht, P; Hoppe, N; Bode, C; et al.
Abstract:  : Metabolic syndrome (MetS) clusters the main risk factors for cardiovascular diseases (CVDs) and endocrine dysfunction. The pathomechanism of MetS is described as local death of hypertrophic adipocytes releasing danger-associated molecular patterns (DAMPs) such as nucleotides (e.g. ADP). This promotes a long term inflammation of adipose tissue via activation of purinergic receptors with a gradual shift towards a pro-inflammatory environment. The ADP receptor P2Y13 is both described in metabolic and immunological processes. These combined characteristics make the P2Y13 an interesting candidate to investigate its role in MetS. Nevertheless, the role of P2Y13R in the pathogenesis of MetS is currently unknown and shall be analyzed in this study. BMDM isolation and differentiation to Mϕ using M-CSF and subsequent stimulation with medium, LPS and IFNγ or IL4; Expression was quantified using Taqman. Male C57Bl6/J wild-type (WT) and P2Y13-deficient (KO) mice were fed a HFD for 20 weeks; body weight and food consumption were recorded weekly. GTT, ITT and metabolic cages were performed after 15 weeks with euthanization after 20 weeks. In order to distinguish the effect of hematopoetic or somatic cells, mice were lethally irradiated with 9.4Gy and reconstituted with donor bone-marrow (BM) via tail vein injection. We observed a unique expression of P2Y13R on pro-inflammatory M1 Mϕ. After HFD feeding KO mice showed higher O2 consumption compared to WT mice (AUC of O2 consumption on 2nd day= KO:61620±2261mL/kg vs WT: 53830±916mL/kg, p<0.05). Although KO mice consumed more food compared to WT littermates (KO:5.7±0.5g/d vs WT:3.1±0.1g/d, p<0.0001), they showed significantly decelerated weight gain (e.g.week 15→KO:147, 292±5, 26% vs WT:180.8±15.9%, p<0.05). Obese KO animals outperformed obese WT littermates in a peritoneal glucose tolerance test (GTT) (2h post-injection (post-i.) →KO:273.7±46.3mg/dL vs WT: 555.0±40.8mg/dL, p<0.05). KO mice on HFD were protected from developing a fatty liver. HFD KO mice receiving WT BM show accelerated weight gain compared to KO mice receiving KO BM (e.g.week 10 WT in KO: 111.2±2.2% vs KO in KO: 102.2±1.2%, p<0.05). In the GTT irradiated KO mice either receiving KO or WT BM are protected from HFD induced impaired glucose homeostasis (45min post-i.; KO→KO:222.1±21.2mg/dL vs WT→KO:232.8±15.9mg/dL vs WT on chow diet:240.4±18.6mg/dL). Contrary, WT mice receiving KO or WT BM developed a glucose resistance comparable to non-irradiated WT mice (45min post-i.; WT→WT:423.8±61.7mg/dL vs KO→WT:434.3±51.1 vs WT on HFD:574.4±7.9). P2Y13 KO improves the outcome of MetS in mice with improved glucose homeostasis, decelerated weight gain, no fatty liver development and better metabolic turnover. BM transplantation experiments suggest a somatic component as possible explanation of these observations. Given these beneficial metabolic effects, we hypothesize that antagonization of P2Y13R could be a promising therapeutic tool in the field of MetS. Funding Acknowledgement: Type of funding source: None